Review of the Government’s Role in Providing Sport Facilities for Educational Institutions - Defany Ifadh Nur Fhadhliah; Herman Subarjah; Sucipto Sucipto (Universitas Negeri Semarang, 2026)
This study aims to analyze the role of central and regional government in providing sports facilities in educational institutions, identify obstacles to policy implementation, and examine international best practices. The study employed a descriptive literature review method, using PRISMA extraction sheet to select articles from Scopus, Tandfonline, and Google Scholar published between 2014 and 2024. The findings highlight three key aspects: (1) funding is the most decisive factor, with Nordic countries succeeding through stable fiscal decentralization, while Indonesia faces limited regional fiscal capacity; (2) institutional coordination influences policy effectiveness, as reflected in Spain's integrated governance model; and (3) integrating facilities with educational functions, as practiced in Japan, increases student participation. Indonesia's challenges in providing sports facilities stem not only from financial constraints but also from low policy priority and the absence of mandatory, structured cross-sectoral coordination mechanisms at both national and local levels. The study emphasizes the need for improved funding, institutional coordination, and integration of sports facilities with educational functions to promote physical activity and improve physical education in Indonesian schools.